(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
When a tall building is subjected to earthquake under the action of lateral loads. Providing a suitable lateral force resisting system has a significant effect on the performance of the RC frame structure. The present study focuses on the study of bracing systems for RC frame structure. The effectiveness of different types of bracing on the RC frame structure has been carried out. For this study, a G+13 storied RC frame structure has been considered and structural behavior has been studied at three seismic zones (III, IV and V). The RC frame structure models are analyzed by Response spectrum and equivalent static method as per IS 1893:2016 (part1) using STAAD Pro software. The structural behavior has been studied using different types of bracing systems such as X bracing, Diagonal bracing, Chevron bracing and Eccentric bracing. A comparative study has been done on parameters story displacement, story drift, base shear, axial force, weight of the structure between braced and un-braced RC frame model. From the study, it has been observed that the lateral displacement and story drift of the braced system decrease in the structure as compared to the un-braced frame in all seismic zones (III, IV and V). Bending moment values in braced frame model get reduced and axial force value in the braced frame model increase as compared to unbraced frame model. It is concluded that the X bracing significantly contribute to structure stiffness as compared to the other bracing system.